Pengaruh Related Party Transaction terhadap Nilai Perusahaan yang Dimediasi oleh Tax Avoidance - Jao, Robert; Tangke, Paulus; Holly, Anthony; Mardiana, Ana; Nontji, Meifilia (LPPM Universitas Putera Batam, 2024)
This research investigates the influence of related party transactions on firm value mediated by tax avoidance. The theory used is agency theory to explain the relationship between variables. The population used is manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020-2022. The data sources used are secondary data in financial reports and annual reports obtained from the Indonesia Stock Exchange and the company's official website. The total sample is 99 company data for three years, selected using purposive sampling. The research results show that related party transactions positively and significantly influence tax avoidance. The research findings also found that tax avoidance has a negative and significant influence on firm value, and related party transactions have a negative and significant influence on firm value. Finally, this research finds that tax avoidance mediates the relationship between related party transactions and firm value.